Současná obchůzková koleda na Smrtnou neděli v Čechách - Thořová, Věra (Lidé města, 2000)
Considerable attention has been devoted in the Czech ethnographic literature to the habit of taking out the figure of Death in the spring pre-Easter time, mostly at the fifth Sunday of fasting (between March 8 and April 11), its genesis, course and development. The taking out of Death was also widespread in the past among all Western Slavs, a part of the German ethnic group and in a similar fashion in a part of eastern and southern Europe. In Bohemia it is regarded as the oldest spring ceremony in the Czech folk customs in general. Its origin dates back to the pre-Christian era, as evidenced by a number of church bans from later times. This shows that the tradition had very strong roots. Most researchers agree that the habit is associated with the spring equinox, when the winter ends and the spring starts. However, there are also views saying that the habit was connected with medieval plague epidemics and it was meant as a protection against the dangerous infection. At present all of the Czech ethnographic literature regards the habit as outdated and forgotten. However, for all of these claims (depicted in a 1982 publication on annual habits) we have arrived at the conclusion that this graceful spring habit has not entirely vanished in Bohemia. However, we have to admit that it is evidently retreating and its appearance in Czech regions is really rare.